Healthcare-associated infections in patients admitted to a cardiological intensive care unit - Farias, Carolina Huller (2020)
Justification and Objectives: Healthcare-associated infections (HAI) affect thousands of people worldwide and are a major cause of complications among hospitalized patients. This study aimed to identify HAI characteristics among patients hospitalized at a cardiac intensive care unit (CICU) in a reference hospital in Santa Catarina from January to December 2017. Methods: This is a descriptive cross-sectional study conducted in the hospital infection control committee (HICC) and intensive care unit (ICU) of the institution. Data were collected from 86 HAI notification forms. All patients admitted to the CICU notified with HAI by the HICC in 2017 were included in the study. Demographic and clinical data were collected from patients’ medical records. Data were tabulated in Microsoft Excel and analyzed by the Statistical Package for the Social Sciences (SPSS) version 18.0. Results: In 2017, HAI incidence was 58.6% and mortality rate 44.8%. The infection was more prevalent among individuals aged between 71 and 80 years (39.6%), and mainly affected the respiratory tract (RTI) (58.1%), the urinary tract (43%), and the bloodstream (30.2%). Pseudomonas aeruginosa (27.9%), Klebsiella pneumoniae (26.7%) and Acinetobacter baumannii (19.8%) were the main etiological agents. Regarding the base pathology, congestive heart failure was the most frequent (19.8%). Conclusion: This study found similar results on the incidence of HAI in CICU to those reported in the literature. Studies have showed permanent education, prevention and control protocols (bundles), and appropriate hand hygiene to be effective actions in reducing infections.